2021
DOI: 10.1111/vru.13030
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic venous collaterals in dogs with congenital intrahepatic portosystemic shunts are associated with focal shunt or hepatic vein narrowing

Abstract: Dogs with congenital intrahepatic portosystemic shunts (IHPSS) occasionally have multiple smaller intrahepatic, tortuous blood vessels surrounding the primary shunt. This study was a retrospective, observational design that was also descriptive and anatomic in nature. Objectives were to characterize vascular morphology in IHPSS dogs presenting with intrahepatic venous collaterals (IVCs) relative to IHPSS dogs without IVCs, and to propose reasons for IVC development. The authors hypothesized that (a) IVCs devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…They may open into the caudal vena cava or any hepatic vein branch. The morphology of ICPSS has been described in detail using CTA in recent studies [ 17 , 18 , 19 , 20 , 21 , 22 ]. In addition, new classification schemes of ICPSS based on their morphology have been proposed [ Table 1 ] [ 18 , 19 ].…”
Section: Classification Of Congenital Portosystemic Shuntsmentioning
confidence: 99%
“…They may open into the caudal vena cava or any hepatic vein branch. The morphology of ICPSS has been described in detail using CTA in recent studies [ 17 , 18 , 19 , 20 , 21 , 22 ]. In addition, new classification schemes of ICPSS based on their morphology have been proposed [ Table 1 ] [ 18 , 19 ].…”
Section: Classification Of Congenital Portosystemic Shuntsmentioning
confidence: 99%
“…Finally, it is unknown how this assessment applies when there is more than one IPSS, including collaterals. 1 In conclusion, using portal CTA, we showed that canine congenital intrahepatic shunts pass between liver lobes in an identifiable fissure (interlobar) or through a specific lobe (intralobar). Interlobar…”
Section: Discussionmentioning
confidence: 66%
“…Although convenient, these classifications might not be reliable descriptors because the divisions have been variably defined in the literature, either by the lobe through which the shunt passes or by the direction the shunt enters the CVC. 1,2,5,22 The two longitudinal fissures that pass through the liver conveniently divide the liver into three groups of lobes. Additionally, the right divisional lobes tend to drain into the right side of the CVC; central divisional lobes, ventral side of the CVC; left divisional lobes, left side of the CVC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations